Paths of research in Religion and Politics: An Introduction - Giorgi, Alberta (2014)
Religion plays an important role in contemporary politics, both as a public and political actor, and as set of values. As a public actor, religion widely participates in the political spheres of European countries. At the same time, both European and non-European societies are experiencing a profound reshaping of their political landscapes. In these contexts, it has become clear that new modes of governance redraw the boundaries between institutional actors and citizens, and create space for horizontal and/or transnational networks. Today, the separation between religion and politics is being questioned more or less radically, and the meaning and the substance of democracy likewise. This special issue aims to offer a wide range of examples of studies focusing on the interactions between religion and politics from different disciplinary perspectives and scientific traditions. Ranging from single case studies to transnational comparative analyses, from sociology of religion to political science, and from the analysis of specific religious traditions to comparative studies, the articles presented offer a useful insight of topics and debates. This heterogeneity allows the readers to have an overview on some of the most important religious actors (movements, associations, groups and, parties in contemporary democracies, such as Christian traditional parties in Europe and the US, Islamist groups in Turkey and in Pakistan. At the same time, this collection of article shows different approaches through which is possible to analyse these movements, such as cross-country comparative approaches, comparison between different cases of religious groups’ collective action within the same national contexts or in the same urban area, or in-depth case studies of the specific role of religious groups in a broader national mobilization. The common element of these different contributions is the objective of looking at the complex relationships between religious organizations (both movements and parties) and political mobilizations, and analysing the religious factor neither as a mere effect of conflicts driven by non-religious factors, such as economic or utilitarian motives, nor as essentialist phenomena driven by non-rational logics of action.